Confnement shape effect on D0 impurity in a GaAs quantum dot with spin-orbit coupling in a magnetic field. (October 2020) - Saini, Pooja; Chatterjee, Ashok
Abstract: The role of the nature of confinement on a neutral hydrogenic donor impurity in a quantum dot is studied using a power-exponential potential in the presence of Rashba and Dresselhaus spin-orbit interactions and an external magnetic field. The ground state energy is calculated variationally and the corresponding binding energy, magnetic moment and susceptibility are obtained as a function of various quantum dot parameters. Highlights: A D 0 complex is studied in a power-exponential (PE) quantum dot with spin-orbit interactions in a magnetic field. Binding energy (BE) and susceptibility (S) of the D 0 complex are obtained variationally. For a small dot, BE shows a peak at a critical value of the steepness parameter ( p ) of the PE potential. BE depends significantly on p only at low magnetic field. | S | increases with p at low magnetic field, while at large field, it decreases.